Research Trends in the Development of Google Sites-Based Learning Media Integrated with PBL to Improve Generic Science Skills (2015-2024): A Systematic Review - Dian Susanti (Balai Publikasi Indonesia, 2026)
This study aims to develop Google Sites-based learning media integrated with Problem-Based Learning (PBL) to improve general scientific skills in science subjects. The study adopted a design-based research approach, focusing on the design, implementation, and evaluation of educational media. The development process involved needs analysis, content creation, and iterative testing with feedback from educators and students. The media was designed to facilitate an interactive and collaborative learning experience, allowing students to engage with real-world problems and apply scientific concepts effectively. Pre- and post-intervention assessments were conducted to measure the impact on students' scientific skills. Results showed significant improvements in both areas, highlighting the effectiveness of using Google Sites as a versatile platform for PBL-oriented science education. The findings suggest that integrating digital tools in the learning environment can encourage higher-order thinking and improve students' overall engagement in science. Future research could explore scalability and adaptability across different educational contexts